Spastic dysphonia - Shyamala Dharmaraj (Journal of All India Institute of Speech and Hearing, 1970)
In 1871 Traube described Spastic Dysphonia as a form of psychogenic hoarse- ness (Aronson et al., 1968 a).  Luchsinger (1967) defines it as 'a disorder of phona- tion characterized by a stained, creaking, choked vocal attack and a tense and squeezed voice accompanied by extreme tension of the entire phonatory system. The stressed vowels are divided into two portions.    It is characteristic that the com- municative function of speech is primarily affected' (p. 328).    The reflex action of phonation remains intact. The patient may not exhibit any trouble in laughing, coughing, singing, speaking to oneself or speaking to children.   During silence, respiration is normal, becoming completely erratic with double starts with violent jerks and wasteful breathing while speaking (Panconcelli-Calzia 1956).    Upper respiratory tract and larynx, on examination, appear normal.   However, continued vocal strain may lead to secondary signs of tissue irritation in the larynx (Brodnitz1961).